Digital Communication in Medical Practice - Finn, Nancy B.; Bria, William F. (Health Informatics, 2009)
In this current technological medical climate, it is vital for healthcare professionals to arm themselves and their patients with as much information as possible. Digital Communication in Medical Practice is a concise overview of the communication tools available to every practicing physician. The book illustrates how proven communication technologies - the computer, email and the Internet, cell phones, PDAs, and video - can help doctors address the issues of too little time, too many patients and too much information. It discusses how digitization of health records makes it easier for doctors and patients to increase continuity of care by managing data collaboratively. The book discusses the convenience and efficiency of email and patient portals, how eliminating telephone tag can result in greater efficiency and better patient communications, and the value of e-prescribing, and telemedicine. It includes issues of security, privacy, and healthcare quality, as well as the legislative initiatives that have been passed to protect healthcare information from unauthorized entry. It evaluates important questions about the cost of health services and how various payment structures impact the doctor's ability to be paid a fair wage. Based around revealing case studies, the book illustrates how communication or the lack thereof can make a significant difference in treatment and outcome. It is a primer in how these important communication technologies save time and money and most importantly will reduce critical medical errors thus saving lives.